Space and territory as categories for understanding the present time: theoretical emergence and conceptual renewal regarding the Chilean October - 2019 - Marchant Santiago, Carla; Monje-Hernández, Yerko (Revista de Humanidades de Valparaíso, 2021)
The mobilization cycle that began in October 2019 represented a crucial moment in the Chilean democratic trajectory. What began as a protest for the rise of 30 Chilean pesos in the Santiago Metro, quickly took on national demand as the horizon exceeded that specific bid, and became a systemic and structural criticism of the democratic institutions and the constitutional, economic, social and cultural structure inherited from the dictatorship. This social awakening in October not only implied transformations associated to material life. Also the conceptual and theoretical tools that were used to understand social phenomena from spaces of intellectual exercise, such as universities were modified. One of these categories is precisely space and territory, which from the nineties with supported and growing socio-environmental movements, was installed in the repertoire of popular demands. A dimension that was also strongly glimpsed in the October protests: the defence of territories as spaces for life. Based on this, a two-dimensional journey is proposed, first a theoretical conceptual debate and on the other hand a historical approach dealing with the emergence of the concept in recent Chilean history, with the interest of understanding a socio-territorial and historical dimension of what happened in October 2019.